Blood biomarker dynamics in people with relapsing multiple sclerosis treated with cladribine tablets: results of the 2-year MAGNIFY-MS study - Heinz Wiendl; Frederik Barkhof; Frederik Barkhof; Xavier Montalban; Anat Achiron; Anat Achiron; Tobias Derfuss; Andrew Chan; Suzanne Hodgkinson; Alexandre Prat; Letizia Leocani; Letizia Leocani; et al. (Frontiers in Immunology)
Background and objectivesCladribine tablets (CladT) represent an effective immune reconstitution therapy, administered in short treatment courses over two consecutive years. To better understand the amplitude of immune changes, we performed a comprehensive analysis during the 2-year study period for the entire MAGNIFY-MS population (N=270). In addition to lymphocyte kinetics, we studied intracellular cytokines serum proteins, and their associations with clinical outcomes. To put these changes into perspective, we analyzed transcriptional changes in T and B cells and associated biological pathways before and after each treatment course with CladT.MethodsImmunophenotyping and transcriptomics were performed at regular visits with major differences reported between baseline (BL) and after each yearly treatment course. Assessments included: lymphocyte dynamics, RNA sequencing (B and T cells), intracellular cytokines, serum proteins (immunoglobulins [IgG and IgM], and serum neurofilament light chain [sNfL]). Clinical measures included: MRI activity, annualized relapse rate (ARR), 6-month confirmed disability progression (6mCDP), timed 25-foot walk (T25FW), and 9-hole peg test (9HPT).ResultsAll B, T and NK cells were reduced at month (M)3 after CladT administration, except regulatory B cells which increased above BL from M3 to M24. Naïve and transitional B cells recovered at M6; all other B and T cell subsets remained below BL levels. Reductions in all NK cell subtypes were observed at M3, CD16lowCD56bright and NKp46 cells reconstituted at M6 and M12 respectively. Changes in genes and pathways associated with innate and adaptive immune response were observed after CladT treatment, along with reductions in pro-inflammatory cytokine-producing B and T cells and increases in anti-inflammatory cytokine-producing T cells. IgG and IgM levels remained above the lower limits of normal in most participants. sNfL levels decreased, remaining reduced by M24. Significant reductions in the annualized combined unique active lesion count occurred from M2 onwards. ARR was 0.11 (95% confidence interval: 0.09,0.15), with 83% participants free of qualifying relapses. Over 90% of participants were free of 6mCDP, around 87% had no confirmed progression on T25FW and 9HPT. No significant correlations were seen between clinical parameters and lymphocyte dynamics to M6. The safety profile was consistent with previous reports.DiscussionDeep longitudinal immunophenotyping, analysis of transcriptional changes, reduction in cells expressing pro-inflammatory cytokines, along with the marker of neuroaxonal damage provide novel and innovative evidence of CladT rebalancing the immune system towards a more homeostatic and less pathogenic state.Clinical Trial Registrationhttps://clinicaltrials.gov/study/, identifier NCT03364036.